Rondas infantiles y el esquema corporal en los niños de inicial II en la Escuela de Educación Básica 18 de Noviembre de la ciudad de Loja, periodo académico 2021-2022 - Castillo Lapo, Jessica Paola (2022)
The body schema is the essential basis to acquire the different learning, as well as to build their own personality and self-affirm themselves, which is why the present work was aimed at determining the incidence of children's rounds in the body schema in children of initial level II of the School of Basic Education November 18 of the City of Loja, academic period 2021-2022; with a quantitative approach, its quasi-experimental design, and descriptive scope, the research methods used were: inductive, deductive and analytical-synthetic, the sample is twenty-eight children of initial II; to whom the psychomotor development test (TEPSI) was applied, the evaluation was carried out with the purpose of detecting problems of the body scheme where it was obtained as a result that 28% of children were at risk level: presenting difficulties of coordination, balance, tempero-spatial orientation and little knowledge of their body schema; Therefore, an alternative proposal called "Singing and dancing we are activating" was designed and applied. It contains forty activities based on children's rounds, which helped the infant to know his body structure, managing to reduce the initial percentage to 16% in risk level, which demonstrates that children's rounds strengthen the acquisition of their movements, body awareness and possibilities of action, which allows the active participation of the child in a spontaneous way. Keywords: body awareness, coordination, image, playful strategy play strategy, rounds.